A high performance polymer composite lithium battery and preparation method thereof
By baking, activation treatment and pressure forming before the semi-finished battery cells of lithium-ion batteries are injected, combined with the steps of secondary packaging, cutting, hot and high-temperature aging, the problem of limited charging rate of lithium-ion batteries during fast charging and discharging is solved, and the effects of high-rate charging and discharging and low battery internal resistance are achieved.
Patent Information
- Application Number
- CN202411985759.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The charging rate of existing lithium-ion batteries is limited during fast charging and discharging, the diffusion and deintercalation rates of electrode materials are slow, and the internal resistance of the battery is high, which cannot meet the needs of high-power discharge equipment.
The semi-finished battery cells are baked before injection to remove moisture, and improve the compatibility of the battery cells and electrolyte; the electrochemical activity of the electrode material is activated through activation treatment and pressure transformation, and a solid electrolyte interface mask is formed to reduce irreversible capacity loss; secondary packaging, cutting and scalding are carried out to enhance the stability of the battery structure; the solid electrolyte interface mask is optimized through high-temperature aging to improve the long-term stable performance of the battery.
It improves the charging and discharging capacity of lithium-ion batteries, reduces the internal resistance of the battery, extends the service life, and achieves the effects of high-rate charging and discharging and low battery internal resistance.
Smart Images

Figure BDA0005222540900000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, in particular to a high-performance polymer composite lithium battery and a preparation method thereof. Background Art
[0002] As an advanced energy storage device, lithium-ion batteries have the advantages of high operating voltage, environmental friendliness and no memory effect. They have been widely used in electric vehicles, rail transportation, aerospace and other fields. However, the energy density of lithium-ion batteries cannot meet the endurance requirements of electronic devices at this stage. Therefore, the development of high-energy-density lithium-ion batteries is an urgent goal in the current energy field. In actual use, many lithium batteries face the dilemma of limited charging and discharging rates. Under the demand for fast charging, some lithium batteries are difficult to efficiently accept the embedding of a large number of lithium ions in a short period of time. This is mainly attributed to the slow diffusion and deintercalation rates of lithium ions in electrode materials, as well as the insufficient interface reaction kinetics between electrodes and electrolytes, which cannot quickly provide enough electrical energy to meet the needs of high-power discharge equipment.
[0003] The resistance of lithium batteries mainly comes from multiple aspects, including the resistance of the electrode material itself, the contact resistance between the electrode and the current collector, and the ion conduction resistance of the electrolyte. In terms of electrode materials, some positive electrode materials such as lithium manganese oxide may undergo structural phase changes during the cycle, resulting in obstruction of the lithium ion conduction channel inside the crystal, thereby increasing the resistance. Insufficient graphene or the presence of impurities in the negative electrode material will also interfere with electronic conduction, thereby increasing the resistance value. At the same time, poor interface bonding between the electrode and the current collector, such as deviations in the coating, pressing and other process links, will form a large contact resistance, which will increase energy loss during current transmission. The ion conduction resistance of the electrolyte is affected by factors such as the type of solvent, lithium salt concentration and temperature. In a low temperature environment, the viscosity of the electrolyte increases, the ion migration rate is significantly reduced, and the internal resistance of the battery rises sharply, seriously affecting the overall performance of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide a high-performance polymer composite lithium battery and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-performance polymer composite lithium battery, which is prepared by baking a semi-finished battery cell before liquid injection, liquid injection, battery cell activation, pressure formation, secondary packaging, cutting, folding, aging, capacity division, boxing and warehousing.
[0006] Furthermore, the semi-finished battery cell is prepared by coating the positive and negative electrode slurries, rolling, slitting, sheeting, winding, shell punching, and side top sealing.
[0007] Furthermore, in the positive and negative electrode slurries, the positive electrode slurry is made of active material, polyvinylidene fluoride, carbon black, and N-methylpyrrolidone; the negative electrode slurry is made of graphene, carbon black, carboxymethyl cellulose, styrene-butadiene rubber, N-methylpyrrolidone, and water.
[0008] Furthermore, the active material is a mixture of any one or more of lithium manganese oxide, lithium nickel manganese cobalt oxide, and lithium cobalt oxide.
[0009] Furthermore, a method for preparing a high-performance polymer composite lithium battery comprises the following preparation steps:
[0010] (1) Baking before liquid injection: clean the inside of the vacuum oven, put the semi-finished battery cell in, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 minute, and nitrogen baking at 85°C for 60 minutes. The second cycle is: vacuum baking at 85°C for 45 minutes, and nitrogen baking at 85°C for 45 minutes. The second cycle is repeated 4 to 7 times. The third cycle is: vacuum baking at 25°C for 1 minute, and nitrogen baking at 25°C for 10 minutes. The third cycle is repeated 4 times. The fourth cycle is: vacuum baking at 25°C for 10 minutes. After baking, cool for 40 minutes to obtain a baked battery cell. The vacuum degree of the vacuum baking is 50Pa to 200Pa.
[0011] (2) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.1 to -0.08 MPa for 1 to 6 seconds, and then the normal pressure is restored. The cycle is repeated 1 to 2 times. Then, the battery cell is pre-sealed at 190 to 210°C and the vacuum degree is -0.01 to -0.08 MPa for 3 to 5 seconds. After the test is qualified, the fully inspected battery cell is obtained.
[0012] (3) Cell activation: Put the fully inspected cells into a material box and activate them at 20-30° C. for 36-72 hours to obtain activated cells;
[0013] (4) Pressure formation: Place the activated battery cell in a high temperature formation cabinet, set the cabinet temperature to 53-63°C, the pressure to 0.05-0.8MPa, first charge at a rate of 0.2C to a cut-off voltage of 3500mV, charge for 30min, then charge at a rate of 0.5C-0.6C to a cut-off voltage of 4050mV, charge for 120-180min, and obtain a formed battery cell;
[0014] (5) Secondary packaging: After the packaging machine is preheated to a temperature of 185-205°C, the formed battery cell is placed in the positioning groove of the secondary packaging machine. The thickness of the bottom gasket and the position of the positioning block are adjusted according to the thickness of the battery cell so that the battery cell fits into the positioning groove. The positioning block is fixed with a hexagonal wrench. The packaging is performed for 5-7 seconds at a vacuum degree of -0.09MPa, a pressure plate pressure of 0.2-0.7MPa, and a packaging tension of 30-50N / 10mm. After the packaging is completed, the secondary sealed battery cell is obtained;
[0015] (6) Cutting, folding and ironing: The two sealed cells are sequentially subjected to cutting, folding and ironing at 150-155°C to obtain semi-finished batteries;
[0016] (7) Aging: The semi-finished battery is placed into a material box and aged at 40-50° C. for 18-30 hours to obtain an aged battery;
[0017] (8) Capacity division, boxing and storage: Place the two pole ears of the aged battery into the corresponding positive and negative electrode fixtures in the capacity division cabinet, let it stand for 5 minutes, charge at a rate of 0.1C~0.6C to a cut-off voltage of 4200mV, let it stand for 5 minutes, discharge at a rate of 0.1C~0.6C to a cut-off voltage of 3000mV, let it stand for another 4 minutes, charge at a rate of 0.1C~0.6C to a cut-off voltage of 3950mV, and terminate the current of 0.01CmA. After capacity division, load it into material boxes, package it and put it into storage to obtain high-performance polymer composite lithium batteries.
[0018] Furthermore, the preparation steps of the semi-finished battery cell in step (1) are as follows:
[0019] a. Preparation of positive electrode slurry: Add N-methylpyrrolidone to a stirring barrel, add polyvinylidene fluoride, stir at 40r / min for 30min, add carbon black, disperse at 1600r / min for 30min, then add active material, continue to disperse for 30min, adjust the slurry viscosity to 6500-9500mPa·s with N-methylpyrrolidone, sieve with a 120-150 mesh screen to obtain a positive electrode slurry; during the stirring and dispersing process, the slurry temperature is 25-55°C and the vacuum degree is -0.1 to -0.08MPa;
[0020] b. Preparation of negative electrode slurry: Add N-methylpyrrolidone to a stirring barrel, add carboxymethyl cellulose, stir at 40r / min for 30min, add carbon black, disperse at 1600r / min for 30min, then add graphene, continue to disperse for 30min, then add styrene-butadiene rubber and deionized water and continue to disperse for 30min, adjust the slurry viscosity to 2000-4000mPa·s with N-methylpyrrolidone, sieve with a 120-mesh screen to obtain a negative electrode slurry; during the stirring and dispersing process, the slurry temperature is 25-55°C and the vacuum degree is -0.1 to -0.08MPa;
[0021] c. Coating: Connect the positive aluminum foil and the negative copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to a moderate level, clamp the baffle plate and the steel rod, add the corresponding slurry to the material tank, set the fan frequency of the coating machine to 45-55Hz, and heat the positive electrode to 105-125℃ and the negative electrode to 95-110℃ for coating to obtain the coated positive and negative electrode sheets;
[0022] d. Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 5 to 20 mm away from the roller edge, pass them at a rolling speed of 1 to 10 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides, let them stand for 2 hours, and then slit them through an automatic slitting machine to obtain positive and negative electrode sheets;
[0023] e. Preparation: The positive and negative electrode sheets, positive and negative tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. The secondary welding is performed at an ultrasonic frequency of 20 to 70 kHz and 0.05 s after welding, and the welding lasts for 0.06 s. The ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, so as to obtain positive and negative electrode formed sheets;
[0024] f. Winding: Place the diaphragm on the reel, pull it to the winding needle in a clockwise direction, place the positive and negative electrode formed sheets in the corresponding material trough, set the semi-automatic winding machine air pressure at 0.4-0.6MPa and the diaphragm welding temperature at 180-200℃, and wind it. After testing that there is no short circuit phenomenon, the winding core is obtained;
[0025] g. Punching: put the aluminum-plastic film into the discharge shaft, set the air pressure of the punching machine to 0.4-0.8MPa, the delay pressure of the booster cylinder to 1-3s, and the delay of the punching top die to 0.5-1.5s, select the corresponding mold according to the production model, and punch the shell automatically to obtain the punched aluminum-plastic film;
[0026] h. Top and side sealing: Place the core into the punched aluminum-plastic film, and perform top sealing, side sealing, corner pre-sealing, and edge trimming in sequence to obtain a semi-finished battery cell.
[0027] Furthermore, when the battery capacity of the semi-finished battery cell in step (1) is ≤3000mAh, the second cycle is baked 4 times, the battery capacity is 3000-5000mAh, the second cycle is baked 5 times, the battery capacity is 5000-7000mAh, the second cycle is baked 6 times, the battery capacity is ≥7000mAh, and the second cycle is baked 7 times.
[0028] Furthermore, the weight ratio of N-methylpyrrolidone, polyvinylidene fluoride, carbon black and active substance in step a is (30-50): (3-7): (2-10): (33-64).
[0029] Furthermore, in step b, the weight ratio of N-methylpyrrolidone, carboxymethyl cellulose, carbon black, graphene, styrene-butadiene rubber and deionized water is (33-55): (2-6): (4-8): (28-42): (1-3): (20-30).
[0030] Furthermore, the parameters of the top seal in step h are as follows: upper mold temperature 190-210°C, lower mold temperature 180-200°C, head pressure 0.3-0.6MPa, and packaging time 3-4s; the parameters of the side seal are as follows: upper mold temperature 175-195°C, lower mold temperature 175-195°C, head pressure 0.3-0.6MPa, and packaging time 2.5-4.0s; the parameters of the corner pre-seal are as follows: upper mold temperature 120-140°C, lower mold temperature 120-140°C, head pressure 0.15-0.3MPa, and packaging time 0.3-1.0s.
[0031] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0032] The present invention bakes the semi-finished battery core before liquid injection to remove moisture in the battery core, avoid the reaction between moisture and lithium salt in the electrolyte, improve the compatibility between the battery core and the electrolyte, and thus improve the comprehensive performance of the battery; after the liquid injection is completed, activation treatment is carried out and formation is carried out under a certain pressure to activate the electrochemical activity of the electrode material, and a layer of solid electrolyte interface film is formed on the negative electrode surface of the battery core to prevent further reaction between the electrolyte and the negative electrode material, reduce irreversible capacity loss, and provide a stable channel for the embedding and de-embedding of lithium ions, so that lithium ions can be smoothly transmitted between the negative electrode and the electrolyte, and the charging and discharging capacity of the battery is improved; then secondary packaging, cutting, folding and ironing treatment are carried out to firmly combine various parts of the battery together, enhance the overall structural stability of the battery, and reduce the risk of short circuit; then high-temperature aging is carried out to further optimize the solid electrolyte interface film formed in the battery formation stage, and the electrolyte inside the battery can better infiltrate the electrode material, improve the long-term stability performance of the battery, and extend the service life; finally, the capacity is divided and the box is packed to obtain a high-performance polymer composite lithium battery, so as to achieve the effects of high-rate charging and discharging capacity, low battery internal resistance and long service life.
[0033] Among them, the semi-finished battery cell first adds active materials and polyvinylidene fluoride to the positive electrode slurry, and adds graphene to the negative electrode slurry, which can provide a higher voltage platform and specific capacity during the charge and discharge process, thereby increasing the energy density of the battery and improving the high-rate charge and discharge capability of the battery. At the same time, polyvinylidene fluoride can form a protective film on the surface of the positive electrode material to prevent dissolution and structural damage. The graphene of the negative electrode serves as a supporting skeleton to prevent the volume expansion and contraction of the negative electrode material during the charge and discharge process, thereby reducing the pulverization and shedding of the electrode material and extending the battery life; then it is coated by an S-shaped multi-roller traction belt, and a pole piece with a uniform coating is formed by controlling the parameters of each roller, so that the potential and current distribution of the battery at different parts are more consistent, reducing the polarization phenomenon caused by excessive local current density, and reducing The internal resistance of the battery is reduced, thereby improving the overall performance consistency of the battery; the pole piece is then rolled with a double-roller machine to reduce the gap between the particles of the coating material, increase the electrode density, and make the lithium ions more efficiently embedded and de-embedded during the charge and discharge process, thereby improving the battery's rate performance; the pole piece and the pole ear are combined into a molded sheet by ultrasonic welding, and the high-frequency vibration causes tiny plastic deformation on the metal surface of the pole ear and the connecting component, reducing the thermal damage to the material caused by traditional welding, while making the contact between the pole piece and the pole ear closer, thereby reducing the internal resistance of the battery and improving the overall performance of the battery; finally, the molded sheet and two diaphragms are wound and then punched into a shell and sealed on the top side to prevent the electrolyte from leaking from the inside of the battery, reduce damage to the internal structure of the battery, prevent problems such as electrode displacement and diaphragm rupture, and effectively extend the battery life. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high-performance polymer composite lithium battery prepared in the following examples.
[0036] Battery internal resistance and rate performance: Take the same number of examples and comparative examples and test them in accordance with QC / T 743.
[0037] Capacity retention rate after 500 cycles: Take the same number of examples and comparative examples, charge and discharge them at a rate of 1C, record the initial discharge capacity and the discharge capacity after 500 cycles, respectively, as Cap1st and Cap500th, and calculate the capacity retention rate after 500 cycles as Cap500th / Cap1st. Test voltage range: 1.4-2.8V.
[0038] Example 1
[0039] (1) Preparation of positive electrode slurry: 30 parts of N-methylpyrrolidone were added to a stirring barrel, and 3 parts of polyvinylidene fluoride were added. After stirring at 40 r / min for 30 min, 2 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Subsequently, 33 parts of lithium cobalt oxide were added, and the dispersion was continued for 30 min. The slurry viscosity was adjusted to 6500 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 150-mesh screen to obtain a positive electrode slurry. During the stirring and dispersing process, the slurry temperature was 25°C and the vacuum degree was -0.1 MPa.
[0040] (2) Preparation of negative electrode slurry: 33 parts of N-methylpyrrolidone were added to a stirring barrel, and 2 parts of carboxymethyl cellulose were added. After stirring at 40 r / min for 30 min, 4 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Then, 28 parts of graphene were added, and the dispersion was continued for 30 min. Then, 1 part of styrene-butadiene rubber and 20 parts of deionized water were added, and the dispersion was continued for 30 min. The slurry viscosity was adjusted to 2000 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 120-mesh screen to obtain a negative electrode slurry. During the stirring and dispersing process, the slurry temperature was 25°C and the vacuum degree was -0.1 MPa.
[0041] (3) Coating: Connect the positive electrode aluminum foil and the negative electrode copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to a moderate level, clamp the baffle plate and the steel rod, add the corresponding slurry to the material tank, set the coating machine fan frequency to 45 Hz, and heat the positive electrode to 105 ° C and the negative electrode to 95 ° C for coating to obtain coated positive and negative electrode sheets;
[0042] (4) Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 5 mm away from the roller edge, pass through at a rolling speed of 1 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides. Let it stand for 2 hours, and then slit it into strips using an automatic slitting machine to obtain positive and negative electrode sheets;
[0043] (5) Sheet making: The positive and negative electrode sheets, positive and negative electrode tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. After welding for 0.05 s at an ultrasonic frequency of 20 kHz, secondary welding is performed for 0.06 s, wherein the ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, to obtain positive and negative electrode formed sheets;
[0044] (6) Winding: Place the diaphragm on the reel and pull it to the winding needle in a clockwise direction. Place the positive and negative electrode formed sheets in the corresponding material troughs. Set the semi-automatic winding machine air pressure at 0.4 MPa and the diaphragm welding temperature at 180°C for winding. After testing for short circuit, the winding core is obtained.
[0045] (7) Punching: Place the aluminum-plastic film on the discharge shaft, set the punching machine air pressure to 0.4 MPa, the booster cylinder delay pressure to 1 second, and the punching top die delay to 0.5 second, select the corresponding mold according to the production model, and punch the shells automatically to obtain the punched aluminum-plastic film.
[0046] (8) Top and side sealing: Place the coil core into the aluminum-plastic film with a shell, and perform top sealing for 3 seconds at an upper mold temperature of 190°C, a lower mold temperature of 180°C, and a head pressure of 0.3 MPa. Then, perform side sealing for 2.5 seconds at an upper mold temperature of 175°C, a lower mold temperature of 175°C, a head pressure of 0.3 MPa, and then perform corner pre-sealing for 0.3 seconds at an upper mold temperature of 120°C, a lower mold temperature of 120°C, a head pressure of 0.15 MPa, and finally perform edge trimming to obtain a semi-finished battery cell.
[0047] (9) Baking before liquid injection: clean the inside of the vacuum oven, put in the semi-finished battery cell with a battery capacity of 2800 mAh, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 min, and nitrogen baking at 85°C for 60 min. The second cycle is: vacuum baking at 85°C for 45 min, and nitrogen baking at 85°C for 45 min. The second cycle is repeated for 4 times. The third cycle is: vacuum baking at 25°C for 1 min, and nitrogen baking at 25°C for 10 min. The third cycle is repeated for 4 times. The fourth cycle is: vacuum baking at 25°C for 10 min. After baking, cool for 40 min to obtain a baked battery cell. The vacuum degree of the vacuum baking is 50 Pa.
[0048] (10) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.1 MPa for 1 second, and then the normal pressure is restored. The cycle is repeated once. Then, the battery cell is pre-sealed at 190°C and vacuum degree of -0.01 MPa for 3 seconds. After passing the test, the fully inspected battery cell is obtained.
[0049] (11) Cell activation: Place the fully inspected cells into a material box and activate them at 20° C. for 36 h to obtain activated cells;
[0050] (12) Pressure formation: The activated cell was placed in a high temperature formation cabinet, and the temperature of the formation cabinet was set to 53°C and the pressure was set to 0.05 MPa. The cell was first charged at a rate of 0.2C to a cut-off voltage of 3500 mV for 30 min, and then charged at a rate of 0.5C to a cut-off voltage of 4050 mV for 120 min to obtain a formed cell.
[0051] (13) Secondary packaging: After the packaging machine temperature reaches 185°C, place the formed battery cell into the positioning groove of the secondary packaging machine, adjust the bottom gasket thickness and the positioning block position according to the thickness of the battery cell, so that the battery cell is just stuck in the positioning groove, use a hexagonal wrench to fix the positioning block, and package for 5s under vacuum degree -0.09MPa, pressure plate air pressure 0.2MPa, and packaging tension 30N / 10mm. After the packaging is completed, the secondary packaged battery cell is obtained;
[0052] (14) Cutting, folding and ironing: Place the two sealed cells in the folding fixing groove, and then perform cutting, folding and ironing at 150°C in sequence to obtain a semi-finished battery;
[0053] (15) Aging: The semi-finished battery is placed into a material box and aged at 40° C. for 18 h to obtain an aged battery;
[0054] (16) Capacity division, packaging and storage: The two pole ears of the aged battery are placed in the corresponding positive and negative electrode fixtures in the capacity division cabinet, left to stand for 5 minutes, and charged at a rate of 0.1C to a cut-off voltage of 4200mV. After standing for 5 minutes, the battery is discharged at a rate of 0.1C to a cut-off voltage of 3000mV. After standing for another 4 minutes, the battery is charged at a rate of 0.1C to a cut-off voltage of 3950mV, with a termination current of 0.01CmA. After capacity division, the battery is loaded into a material box, packaged and stored to obtain a high-performance polymer composite lithium battery.
[0055] Example 2
[0056] (1) Preparation of positive electrode slurry: 40 parts of N-methylpyrrolidone were added to a stirring barrel, and 5 parts of polyvinylidene fluoride were added. After stirring at 40 r / min for 30 min, 6 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Subsequently, 49 parts of lithium nickel manganese cobalt oxide were added, and the dispersion was continued for 30 min. The slurry viscosity was adjusted to 8000 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 150-mesh screen to obtain a positive electrode slurry. During the stirring and dispersing process, the slurry temperature was 40°C and the vacuum degree was -0.09 MPa.
[0057] (2) Preparation of negative electrode slurry: 44 parts of N-methylpyrrolidone were added to a stirring barrel, and 4 parts of carboxymethyl cellulose were added. After stirring at 40 r / min for 30 min, 6 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Then 35 parts of graphene were added, and the dispersion was continued for 30 min. Then 2 parts of styrene-butadiene rubber and 25 parts of deionized water were added, and the dispersion was continued for 30 min. The slurry viscosity was adjusted to 3000 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 120-mesh screen to obtain a negative electrode slurry. During the stirring and dispersing process, the slurry temperature was 40°C and the vacuum degree was -0.09 MPa.
[0058] (3) Coating: Connect the positive electrode aluminum foil and the negative electrode copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to be appropriate, clamp the baffle plate and the steel rod, add the corresponding slurry to the material tank, set the coating machine fan frequency to 50 Hz, and heat the positive electrode to 115 ° C and the negative electrode to 105 ° C for coating to obtain the coated positive and negative electrode sheets;
[0059] (4) Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 12.5 mm away from the roller edge, pass through at a rolling speed of 5.5 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides. Let it stand for 2 hours, and then slit it into strips using an automatic slitting machine to obtain positive and negative electrode sheets;
[0060] (5) Sheet making: The positive and negative electrode sheets, positive and negative electrode tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. After welding for 0.05 s at an ultrasonic frequency of 45 kHz, secondary welding is performed for 0.06 s, wherein the ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, to obtain positive and negative electrode formed sheets;
[0061] (6) Winding: Place the diaphragm on the reel and pull it to the winding needle in a clockwise direction. Place the positive and negative electrode formed sheets in the corresponding material troughs. Set the semi-automatic winding machine air pressure at 0.5 MPa and the diaphragm welding temperature at 190°C for winding. After testing for short circuit, the winding core is obtained.
[0062] (7) Punching: Place the aluminum-plastic film on the discharge shaft, set the punching machine air pressure to 0.6 MPa, the booster cylinder delay pressure to 2 s, and the punching top die delay to 1.0 s, select the corresponding mold according to the production model, and punch the shells automatically to obtain the punched aluminum-plastic film.
[0063] (8) Top and side sealing: Place the coil core into the aluminum-plastic film with a shell, and perform top sealing for 3.5 seconds at an upper mold temperature of 200°C, a lower mold temperature of 190°C, a head sealing pressure of 0.45 MPa, and side sealing for 3.3 seconds at an upper mold temperature of 185°C, a lower mold temperature of 185°C, a head sealing pressure of 0.45 MPa, and corner pre-sealing for 0.65 seconds. Finally, trim the edges to obtain a semi-finished battery cell.
[0064] (9) Baking before liquid injection: clean the inside of the vacuum oven, put in the semi-finished battery cell with a battery capacity of 6200mAh, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 minute, and nitrogen baking at 85°C for 60 minutes. The second cycle is: vacuum baking at 85°C for 45 minutes, and nitrogen baking at 85°C for 45 minutes. The second cycle is repeated for 6 times. The third cycle is: vacuum baking at 25°C for 1 minute, and nitrogen baking at 25°C for 10 minutes. The third cycle is repeated for 4 times. The fourth cycle is: vacuum baking at 25°C for 10 minutes. After baking, cool for 40 minutes to obtain a baked battery cell. The vacuum degree of the vacuum baking is 125Pa.
[0065] (10) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.09 MPa for 3.5 seconds, and then the normal pressure is restored. The cycle is repeated once. Then, the battery cell is pre-sealed at 200°C and vacuum degree of -0.09 MPa for 4 seconds. After passing the test, the fully inspected battery cell is obtained.
[0066] (11) Cell activation: Place the fully inspected cells into a material box and activate them at 25° C. for 54 h to obtain activated cells;
[0067] (12) Pressure formation: The activated cell was placed in a high temperature formation cabinet, and the temperature of the formation cabinet was set to 55°C and the pressure was set to 0.23 MPa. The cell was first charged at a rate of 0.2C to a cut-off voltage of 3500 mV for 30 min, and then charged at a rate of 0.5C to a cut-off voltage of 4050 mV for 135 min to obtain a formed cell.
[0068] (13) Secondary packaging: After the packaging machine temperature reaches 195°C, place the formed battery cell into the positioning groove of the secondary packaging machine, adjust the bottom gasket thickness and the positioning block position according to the thickness of the battery cell, so that the battery cell is just stuck in the positioning groove, use a hexagonal wrench to fix the positioning block, and package for 6s under vacuum degree -0.09MPa, pressure plate air pressure 0.45MPa, packaging tension 40N / 10mm. After the packaging is completed, the secondary packaged battery cell is obtained;
[0069] (14) Cutting, folding and ironing: Place the two sealed cells in the folding fixing groove, and then perform cutting, folding and ironing at 152.5°C to obtain a semi-finished battery;
[0070] (15) Aging: The semi-finished battery is placed into a material box and aged at 45° C. for 24 h to obtain an aged battery;
[0071] (16) Capacity division, packaging and storage: The two pole ears of the aged battery are placed in the corresponding positive and negative electrode fixtures in the capacity division cabinet, left to stand for 5 minutes, and charged at a rate of 0.2C to a cut-off voltage of 4200mV. After standing for 5 minutes, the battery is discharged at a rate of 0.2C to a cut-off voltage of 3000mV. After standing for another 4 minutes, the battery is charged at a rate of 0.2C to a cut-off voltage of 3950mV, with a termination current of 0.01CmA. After capacity division, the battery is loaded into a material box, packaged and stored to obtain a high-performance polymer composite lithium battery.
[0072] Example 3
[0073] (1) Preparation of positive electrode slurry: 50 parts of N-methylpyrrolidone were added to a stirring barrel, and 7 parts of polyvinylidene fluoride were added. After stirring at 40 r / min for 30 min, 10 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Subsequently, 64 parts of lithium manganate were added and dispersed for another 30 min. The slurry viscosity was adjusted to 9500 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 120-mesh screen to obtain a positive electrode slurry. During the stirring and dispersing process, the slurry temperature was 55°C and the vacuum degree was -0.08 MPa.
[0074] (2) Preparation of negative electrode slurry: 55 parts of N-methylpyrrolidone were added to a stirring barrel, and 6 parts of carboxymethyl cellulose were added. After stirring at 40 r / min for 30 min, 8 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Then 42 parts of graphene were added, and the dispersion continued for 30 min. Then 3 parts of styrene-butadiene rubber and 30 parts of deionized water were added, and the dispersion continued for 30 min. The slurry viscosity was adjusted to 4000 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 120-mesh screen to obtain a negative electrode slurry. During the stirring and dispersing process, the slurry temperature was 55°C and the vacuum degree was -0.08 MPa.
[0075] (3) Coating: Connect the positive electrode aluminum foil and the negative electrode copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to be appropriate, clamp the baffle plate and the steel rod, add the corresponding slurry to the material tank, set the coating machine fan frequency to 55 Hz, and heat the positive electrode to 125 ° C and the negative electrode to 110 ° C for coating to obtain coated positive and negative electrode sheets;
[0076] (4) Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 20 mm away from the roller edge, pass through at a rolling speed of 10 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides. Let it stand for 2 hours, and then slit it into strips using an automatic slitting machine to obtain positive and negative electrode sheets;
[0077] (5) Sheet making: The positive and negative electrode sheets, positive and negative electrode tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. After welding for 0.05 s at an ultrasonic frequency of 70 kHz, secondary welding is performed for 0.06 s, wherein the ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, to obtain positive and negative electrode formed sheets;
[0078] (6) Winding: Place the diaphragm on the reel and pull it to the winding needle in a clockwise direction. Place the positive and negative electrode formed sheets in the corresponding material troughs. Set the semi-automatic winding machine air pressure at 0.6 MPa and the diaphragm welding temperature at 200 °C for winding. After testing for short circuit, the winding core is obtained.
[0079] (7) Punching: Place the aluminum-plastic film on the discharge shaft, set the air pressure of the punching machine to 0.8 MPa, the delay pressure of the booster cylinder to 3s, and the delay of the punching top mold to 1.5s. Select the corresponding mold according to the production model, and punch the shells automatically to obtain the punched aluminum-plastic film.
[0080] (8) Top and side sealing: Place the coil core into the aluminum-plastic film with a shell, and perform top sealing for 4 seconds at an upper mold temperature of 210°C, a lower mold temperature of 200°C, and a head pressure of 0.6 MPa. Then, perform side sealing for 4.0 seconds at an upper mold temperature of 195°C, a lower mold temperature of 195°C, a head pressure of 0.6 MPa, and then perform corner pre-sealing for 1.0 seconds at an upper mold temperature of 140°C, a lower mold temperature of 140°C, a head pressure of 0.3 MPa, and finally perform edge trimming to obtain a semi-finished battery cell.
[0081] (9) Baking before liquid injection: clean the inside of the vacuum oven, put in the semi-finished battery cell with a battery capacity of 9100 mAh, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 min, and nitrogen baking at 85°C for 60 min. The second cycle is: vacuum baking at 85°C for 45 min, and nitrogen baking at 85°C for 45 min. The second cycle is repeated 7 times. The third cycle is: vacuum baking at 25°C for 1 min, and nitrogen baking at 25°C for 10 min. The third cycle is repeated 4 times. The fourth cycle is: vacuum baking at 25°C for 10 min. After baking, cool for 40 min to obtain a baked battery cell. The vacuum degree of the vacuum baking is 200 Pa.
[0082] (10) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.08 MPa for 6 seconds, and then the normal pressure is restored. The cycle is repeated twice. Then, the battery cell is pre-sealed at 210°C and vacuum degree of -0.08 MPa for 5 seconds. After passing the test, the fully inspected battery cell is obtained.
[0083] (11) Cell activation: Place the fully inspected cells into a material box and activate them at 30° C. for 72 h to obtain activated cells;
[0084] (12) Pressure formation: The activated cell was placed in a high temperature formation cabinet, and the temperature of the formation cabinet was set to 58°C and the pressure was set to 0.42 MPa. The cell was first charged at a rate of 0.2C to a cut-off voltage of 3500 mV for 30 min, and then charged at a rate of 0.5C to a cut-off voltage of 4050 mV for 150 min to obtain a formed cell.
[0085] (13) Secondary packaging: After the packaging machine temperature reaches 205°C, the formed battery cell is placed in the positioning groove of the secondary packaging machine. The thickness of the bottom gasket and the position of the positioning block are adjusted according to the thickness of the battery cell so that the battery cell is just inserted into the positioning groove. The positioning block is fixed with a hexagonal wrench. The packaging is performed for 7 seconds under a vacuum degree of -0.09MPa, a pressure plate air pressure of 0.7MPa, and a packaging tension of 50N / 10mm. After the packaging is completed, the secondary sealed battery cell is obtained;
[0086] (14) Cutting, folding and ironing: Place the two sealed cells in the folding fixing groove, and then perform cutting, folding and ironing at 155°C to obtain a semi-finished battery;
[0087] (15) Aging: The semi-finished battery is placed into a material box and aged at 50° C. for 30 h to obtain an aged battery;
[0088] (16) Capacity division, packaging and storage: The two pole ears of the aged battery are placed in the corresponding positive and negative electrode fixtures in the capacity division cabinet, left to stand for 5 minutes, and charged at a rate of 0.3C to a cut-off voltage of 4200mV. After standing for 5 minutes, the battery is discharged at a rate of 0.3C to a cut-off voltage of 3000mV. After standing for another 4 minutes, the battery is charged at a rate of 0.3C to a cut-off voltage of 3950mV, with a termination current of 0.01CmA. After capacity division, the battery is loaded into a material box, packaged and stored to obtain a high-performance polymer composite lithium battery.
[0089] Example 4
[0090] (1) Preparation of positive electrode slurry: 35 parts of N-methylpyrrolidone were added to a stirring barrel, and 4.5 parts of polyvinylidene fluoride were added. After stirring at 40 r / min for 30 min, 4 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Subsequently, 42 parts of lithium manganate were added and dispersed for another 30 min. The slurry viscosity was adjusted to 7000 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 130-mesh screen to obtain a positive electrode slurry. During the stirring and dispersing process, the slurry temperature was 35° C. and the vacuum degree was -0.085 MPa.
[0091] (2) Preparation of negative electrode slurry: 40 parts of N-methylpyrrolidone were added to a stirring barrel, and 3 parts of carboxymethyl cellulose were added. After stirring at 40 r / min for 30 min, 5 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Then 33 parts of graphene were added, and the dispersion continued for 30 min. Then 1.5 parts of styrene-butadiene rubber and 23 parts of deionized water were added, and the dispersion continued for 30 min. The slurry viscosity was adjusted to 2500 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 120-mesh screen to obtain a negative electrode slurry. During the stirring and dispersing process, the slurry temperature was 35°C and the vacuum degree was -0.085 MPa.
[0092] (3) Coating: Connect the positive electrode aluminum foil and the negative electrode copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to a moderate level, clamp the baffle plate and the steel rod, add the corresponding slurry into the material tank, set the coating machine fan frequency to 48 Hz, and heat the positive electrode to 110 ° C and the negative electrode to 100 ° C for coating to obtain coated positive and negative electrode sheets;
[0093] (4) Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 10 mm away from the roller edge, pass through at a rolling speed of 4 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides. Let it stand for 2 hours, and then slit it into strips using an automatic slitting machine to obtain positive and negative electrode sheets;
[0094] (5) Sheeting: The positive and negative electrode sheets, positive and negative electrode tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. After welding for 0.05 s at an ultrasonic frequency of 30 kHz, secondary welding is performed for 0.06 s, wherein the ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, to obtain positive and negative electrode formed sheets;
[0095] (6) Winding: Place the diaphragm on the reel and pull it to the winding needle in a clockwise direction. Place the positive and negative electrode formed sheets in the corresponding material troughs. Set the semi-automatic winding machine air pressure at 0.45 MPa and the diaphragm welding temperature at 185 °C for winding. After testing for short circuit, the winding core is obtained.
[0096] (7) Punching: Place the aluminum-plastic film on the discharge shaft, set the punching machine air pressure to 0.5 MPa, the booster cylinder delay pressure to 1.5 s, and the punching top die delay to 0.8 s, select the corresponding die according to the production model, and punch the shell automatically to obtain the punched aluminum-plastic film;
[0097] (8) Top and side sealing: Place the coil core into the aluminum-plastic film with a shell, and seal the top for 3.3 seconds at an upper mold temperature of 197°C, a lower mold temperature of 186°C, and a head pressure of 0.4 MPa. Seal the sides for 3.2 seconds at an upper mold temperature of 180°C, a lower mold temperature of 183°C, a head pressure of 0.4 MPa, and pre-seal the corners for 0.5 seconds at 125°C, a lower mold temperature of 128°C, a head pressure of 0.2 MPa, and trim the edges to obtain semi-finished battery cells.
[0098] (9) Baking before liquid injection: clean the inside of the vacuum oven, put in the semi-finished battery cell with a battery capacity of 4000 mAh, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 min, and nitrogen baking at 85°C for 60 min. The second cycle is: vacuum baking at 85°C for 45 min, and nitrogen baking at 85°C for 45 min. The second cycle is repeated for 5 times. The third cycle is: vacuum baking at 25°C for 1 min, and nitrogen baking at 25°C for 10 min. The third cycle is repeated for 4 times. The fourth cycle is: vacuum baking at 25°C for 10 min. After baking, cool for 40 min to obtain a baked battery cell. The vacuum degree of the vacuum baking is 100 Pa.
[0099] (10) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.085 MPa for 3 seconds, and then the normal pressure is restored. The cycle is repeated once. Then, the battery cell is pre-sealed at 195°C and the vacuum degree is -0.085 MPa for 3.8 seconds. After the test is qualified, the fully inspected battery cell is obtained.
[0100] (11) Cell activation: Place the fully inspected cells into a material box and activate them at 23° C. for 48 h to obtain activated cells;
[0101] (12) Pressure formation: The activated cell was placed in a high temperature formation cabinet, and the temperature of the formation cabinet was set to 60°C and the pressure was set to 0.61 MPa. The cell was first charged at a rate of 0.2C to a cut-off voltage of 3500 mV for 30 min, and then charged at a rate of 0.6C to a cut-off voltage of 4050 mV for 165 min to obtain a formed cell.
[0102] (13) Secondary packaging: After the packaging machine is preheated to 190°C, the formed battery cell is placed in the positioning groove of the secondary packaging machine. The thickness of the bottom gasket and the position of the positioning block are adjusted according to the thickness of the battery cell so that the battery cell fits into the positioning groove. The positioning block is fixed with a hexagonal wrench. The packaging is performed for 5.5 seconds at a vacuum degree of -0.09MPa, a pressure plate pressure of 0.4MPa, and a packaging tension of 35N / 10mm. After the packaging is completed, the excess airbag bag is cut off to obtain the secondary sealed battery cell.
[0103] (14) Cutting, folding and ironing: The two sealed cells are sequentially subjected to cutting, folding and ironing at 152°C to obtain semi-finished batteries;
[0104] (15) Aging: The semi-finished battery is placed into a material box and aged at 42° C. for 24 h to obtain an aged battery;
[0105] (16) Capacity division, packaging and storage: The two pole ears of the aged battery are placed in the corresponding positive and negative electrode fixtures in the capacity division cabinet, left to stand for 5 minutes, and charged at a rate of 0.4C to a cut-off voltage of 4200mV. After standing for 5 minutes, the battery is discharged at a rate of 0.4C to a cut-off voltage of 3000mV. After standing for another 4 minutes, the battery is charged at a rate of 0.4C to a cut-off voltage of 3950mV, with a termination current of 0.01CmA. After capacity division, the battery is loaded into a material box, packaged and stored to obtain a high-performance polymer composite lithium battery.
[0106] Example 5
[0107] (1) Preparation of positive electrode slurry: 45 parts of N-methylpyrrolidone were added to a stirring barrel, and 5.5 parts of polyvinylidene fluoride were added. After stirring at 40 r / min for 30 min, 5 parts of carbon black were added, and dispersed at 1600 r / min for 30 min. Subsequently, 46 parts of active material were added, and the dispersion was continued for 30 min. The slurry viscosity was adjusted to 7600 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 130-mesh screen to obtain a positive electrode slurry. During the stirring and dispersing process, the slurry temperature was 38°C and the vacuum degree was -0.095 MPa.
[0108] (2) Preparation of negative electrode slurry: 42 parts of N-methylpyrrolidone were added to a stirring barrel, and 3.7 parts of carboxymethyl cellulose were added. After stirring at 40 r / min for 30 min, 6 parts of carbon black were added and dispersed at 1600 r / min for 30 min. Then 34 parts of graphene were added and dispersed for 30 min. Then 1 part of styrene-butadiene rubber and 24 parts of deionized water were added and dispersed for 30 min. The slurry viscosity was adjusted to 2800 mPa·s with N-methylpyrrolidone, and the slurry was sieved with a 120-mesh screen to obtain a negative electrode slurry. During the stirring and dispersing process, the slurry temperature was 38°C and the vacuum degree was -0.095 MPa.
[0109] (3) Coating: Connect the positive electrode aluminum foil and the negative electrode copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to be appropriate, clamp the baffle plate and the steel rod, add the corresponding slurry to the material tank, set the coating machine fan frequency to 49 Hz, the positive electrode heating temperature to 110 ° C, and the negative electrode heating temperature to 101 ° C for coating, and obtain the coated positive and negative electrode sheets;
[0110] (4) Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 11 mm away from the roller edge, pass through at a rolling speed of 4.5 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides. Let it stand for 2 hours, and then slit it into strips using an automatic slitting machine to obtain positive and negative electrode sheets;
[0111] (5) Sheeting: The positive and negative electrode sheets, positive and negative electrode tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. After welding for 0.05 s at an ultrasonic frequency of 40 kHz, secondary welding is performed for 0.06 s, wherein the ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, to obtain positive and negative electrode formed sheets;
[0112] (6) Winding: Place the diaphragm on the reel and pull it to the winding needle in a clockwise direction. Place the positive and negative electrode formed sheets in the corresponding material troughs. Set the semi-automatic winding machine air pressure at 0.5 MPa and the diaphragm welding temperature at 188°C for winding. After testing for short circuit, the winding core is obtained.
[0113] (7) Punching: Place the aluminum-plastic film on the discharge shaft, set the punching machine air pressure to 0.55 MPa, the booster cylinder delay pressure to 1.8 s, and the punching top die delay to 0.9 s, select the corresponding die according to the production model, and punch the shell automatically to obtain the punched aluminum-plastic film;
[0114] (8) Top and side sealing: Place the coil core into the aluminum-plastic film with a shell, and seal the top for 3.4 seconds at an upper mold temperature of 198°C, a lower mold temperature of 188°C, and a head pressure of 0.42 MPa. Seal the sides for 3.1 seconds at an upper mold temperature of 182°C, a lower mold temperature of 182°C, a head pressure of 0.42 MPa, and pre-seal the corners for 0.58 seconds at 128°C, a lower mold temperature of 128°C, a head pressure of 0.22 MPa, and trim the edges to obtain semi-finished battery cells.
[0115] (9) Baking before liquid injection: clean the inside of the vacuum oven, put in the semi-finished battery cell with a battery capacity of 5400mAh, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 minute, and nitrogen baking at 85°C for 60 minutes. The second cycle is: vacuum baking at 85°C for 45 minutes, and nitrogen baking at 85°C for 45 minutes. The second cycle is repeated for 6 times. The third cycle is: vacuum baking at 25°C for 1 minute, and nitrogen baking at 25°C for 10 minutes. The third cycle is repeated for 4 times. The fourth cycle is: vacuum baking at 25°C for 10 minutes. After baking, cool for 40 minutes to obtain a baked battery cell. The vacuum degree of the vacuum baking is 120Pa.
[0116] (10) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.095 MPa for 3.3 seconds, and then the normal pressure is restored. The cycle is repeated twice. Then, the battery cell is pre-sealed at 198°C and the vacuum degree is -0.095 MPa for 3.8 seconds. After passing the test, the fully inspected battery cell is obtained.
[0117] (11) Cell activation: Place the fully inspected cells into a material box and activate them at 24° C. for 51 h to obtain activated cells;
[0118] (12) Pressure formation: The activated cell was placed in a high temperature formation cabinet, and the temperature of the formation cabinet was set to 63°C and the pressure was set to 0.8 MPa. The cell was first charged at a rate of 0.2C to a cut-off voltage of 3500 mV for 30 min, and then charged at a rate of 0.6C to a cut-off voltage of 4050 mV for 180 min to obtain a formed cell.
[0119] (13) Secondary packaging: After the packaging machine is preheated to 193°C, the formed battery cell is placed in the positioning groove of the secondary packaging machine. The thickness of the bottom gasket and the position of the positioning block are adjusted according to the thickness of the battery cell so that the battery cell fits into the positioning groove. The positioning block is fixed with a hexagonal wrench. The packaging is performed for 5.8 seconds at a vacuum degree of -0.09MPa, a pressure plate pressure of 0.40MPa, and a packaging tension of 38N / 10mm. After the packaging is completed, the excess airbag bag is cut off to obtain the secondary sealed battery cell.
[0120] (14) Cutting, folding and ironing: The two sealed cells are sequentially subjected to cutting, folding and ironing at 152°C to obtain semi-finished batteries;
[0121] (15) Aging: The semi-finished battery is placed into a material box and aged at 44° C. for 22 h to obtain an aged battery;
[0122] (16) Capacity division, packaging and storage: The two pole ears of the aged battery are placed in the corresponding positive and negative electrode fixtures in the capacity division cabinet, left to stand for 5 minutes, and charged at a rate of 0.6C to a cut-off voltage of 4200mV. After standing for 5 minutes, the battery is discharged at a rate of 0.6C to a cut-off voltage of 3000mV. After standing for another 4 minutes, the battery is charged at a rate of 0.6C to a cut-off voltage of 3950mV, with a termination current of 0.01CmA. After capacity division, the battery is loaded into a material box, packaged and stored to obtain a high-performance polymer composite lithium battery.
[0123] Effect example
[0124] Table 1 below shows the performance analysis results of the high performance polymer composite lithium batteries using Examples 1 to 5 of the present invention.
[0125] Table 1
[0126]
[0127] From the experimental data of Examples 1 to 5 in the above table, it can be found that the high-performance polymer composite lithium battery prepared by the present application has low battery internal resistance and high rate charge and discharge performance, and the capacity retention rate is still high after 500 cycles.
[0128] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high-performance polymer composite lithium battery, characterized in that: The high-performance polymer composite lithium battery is prepared from semi-finished battery cells through the steps of pre-liquidation baking, liquid injection, battery cell activation, pressure formation, secondary packaging, cutting, folding, ironing, aging, capacity division, boxing and storage.
2. A high performance polymer composite lithium battery according to claim 1, characterized in that: The semi-finished battery cell is prepared by coating the positive and negative electrode slurries, rolling, slitting, sheeting, winding, shell punching and side top sealing.
3. A high performance polymer composite lithium battery according to claim 2, characterized in that: In the positive and negative electrode slurries, the positive electrode slurry is prepared from active material, polyvinylidene fluoride, carbon black, and N-methylpyrrolidone; the negative electrode slurry is prepared from graphene, carbon black, carboxymethyl cellulose, styrene-butadiene rubber, N-methylpyrrolidone, and water.
4. A high performance polymer composite lithium battery according to claim 3, characterized in that: The active material is a mixture of any one or more of lithium manganese oxide, lithium nickel manganese cobalt oxide, and lithium cobalt oxide.
5. A method for preparing a high-performance polymer composite lithium battery, characterized in that: The method comprises the following preparation steps: (1) Baking before liquid injection: clean the inside of the vacuum oven, put the semi-finished battery cell in, and perform four cycles of baking. The first cycle is: vacuum baking at 85°C for 1 minute, and nitrogen baking at 85°C for 60 minutes. The second cycle is: vacuum baking at 85°C for 45 minutes, and nitrogen baking at 85°C for 45 minutes. The second cycle is repeated 4 to 7 times. The third cycle is: vacuum baking at 25°C for 1 minute, and nitrogen baking at 25°C for 10 minutes. The third cycle is repeated 4 times. The fourth cycle is: vacuum baking at 25°C for 10 minutes. After baking, cool for 40 minutes to obtain a baked battery cell. The vacuum degree of the vacuum baking is 50Pa to 200Pa. (2) Liquid injection: The baked battery cell is injected with liquid. After the injection is completed, the vacuum degree is maintained at -0.1 to -0.08 MPa for 1 to 6 seconds, and then the normal pressure is restored. The cycle is repeated 1 to 2 times. Then, the battery cell is pre-sealed at 190 to 210°C and the vacuum degree is -0.01 to -0.08 MPa for 3 to 5 seconds. After the test is qualified, the fully inspected battery cell is obtained. (3) Cell activation: Put the fully inspected cells into a material box and activate them at 20-30° C. for 36-72 hours to obtain activated cells; (4) Pressure formation: Place the activated battery cell in a high temperature formation cabinet, set the cabinet temperature to 53-63°C, the pressure to 0.05-0.8MPa, first charge at a rate of 0.2C to a cut-off voltage of 3500mV, charge for 30min, then charge at a rate of 0.5C-0.6C to a cut-off voltage of 4050mV, charge for 120-180min, and obtain a formed battery cell; (5) Secondary packaging: After the packaging machine is preheated to a temperature of 185-205°C, the formed battery cell is placed in the positioning groove of the secondary packaging machine. The thickness of the bottom gasket and the position of the positioning block are adjusted according to the thickness of the battery cell so that the battery cell fits into the positioning groove. The positioning block is fixed with a hexagonal wrench. The packaging is performed for 5-7 seconds at a vacuum degree of -0.09MPa, a pressure plate pressure of 0.2-0.7MPa, and a packaging tension of 30-50N / 10mm. After the packaging is completed, the secondary sealed battery cell is obtained; (6) Cutting, folding and ironing: The two sealed cells are sequentially subjected to cutting, folding and ironing at 150-155°C to obtain semi-finished batteries; (7) Aging: The semi-finished battery is placed into a material box and aged at 40-50° C. for 18-30 hours to obtain an aged battery; (8) Capacity division, boxing and storage: Place the two pole ears of the aged battery into the corresponding positive and negative electrode fixtures in the capacity division cabinet, let it stand for 5 minutes, charge at a rate of 0.1C~0.6C to a cut-off voltage of 4200mV, let it stand for 5 minutes, discharge at a rate of 0.1C~0.6C to a cut-off voltage of 3000mV, let it stand for another 4 minutes, charge at a rate of 0.1C~0.6C to a cut-off voltage of 3950mV, and terminate the current of 0.01CmA. After capacity division, load it into material boxes, package it and put it into storage to obtain high-performance polymer composite lithium batteries.
6. The method for preparing a high-performance polymer composite lithium battery according to claim 5, characterized in that: The preparation steps of the semi-finished battery cell in step (1) are as follows: a. Preparation of positive electrode slurry: Add N-methylpyrrolidone to a stirring barrel, add polyvinylidene fluoride, stir at 40r / min for 30min, add carbon black, disperse at 1600r / min for 30min, then add active material, continue to disperse for 30min, adjust the slurry viscosity to 6500-9500mPa·s with N-methylpyrrolidone, sieve with a 120-150 mesh screen to obtain a positive electrode slurry; during the stirring and dispersing process, the slurry temperature is 25-55°C and the vacuum degree is -0.1 to -0.08MPa; b. Preparation of negative electrode slurry: Add N-methylpyrrolidone to a stirring barrel, add carboxymethyl cellulose, stir at 40r / min for 30min, add carbon black, disperse at 1600r / min for 30min, then add graphene, continue to disperse for 30min, then add styrene-butadiene rubber and deionized water and continue to disperse for 30min, adjust the slurry viscosity to 2000-4000mPa·s with N-methylpyrrolidone, sieve with a 120-mesh screen to obtain a negative electrode slurry; during the stirring and dispersing process, the slurry temperature is 25-55°C and the vacuum degree is -0.1 to -0.08MPa; c. Coating: Connect the positive aluminum foil and the negative copper foil to the multi-roller traction belt with adhesive tape, adjust the distance between the loading plate and the steel rod to a moderate level, clamp the baffle plate and the steel rod, add the corresponding slurry to the material tank, set the fan frequency of the coating machine to 45-55Hz, and heat the positive electrode to 105-125℃ and the negative electrode to 95-110℃ for coating to obtain the coated positive and negative electrode sheets; d. Rolling and slitting: Place the coated positive and negative electrode sheets on a roller 5 to 20 mm away from the roller edge, pass them at a rolling speed of 1 to 10 m / min, and adjust the edge material slitting device to cut the electrode sheets with 4 mm of empty foil on both sides, let them stand for 2 hours, and then slit them through an automatic slitting machine to obtain positive and negative electrode sheets; e. Preparation: The positive and negative electrode sheets, positive and negative tabs, and adhesive tape are passed through the corresponding guide rails at a sheet pulling speed of 100 mm / sec, a tab pulling speed of 80 mm / sec, and a slicing speed of 90 mm / sec. The secondary welding is performed at an ultrasonic frequency of 20 to 70 kHz and 0.05 s after welding, and the welding lasts for 0.06 s. The ultrasonic welding length is 21 mm, the tab length after slicing is 40 mm, and the electrode length is 101 mm, so as to obtain positive and negative electrode formed sheets; f. Winding: Place the diaphragm on the reel, pull it to the winding needle in a clockwise direction, place the positive and negative electrode formed sheets in the corresponding material trough, set the semi-automatic winding machine air pressure at 0.4-0.6MPa and the diaphragm welding temperature at 180-200℃, and wind it. After testing that there is no short circuit phenomenon, the winding core is obtained; g. Punching: put the aluminum-plastic film into the discharge shaft, set the air pressure of the punching machine to 0.4-0.8MPa, the delay pressure of the booster cylinder to 1-3s, and the delay of the punching top die to 0.5-1.5s, select the corresponding mold according to the production model, and punch the shell automatically to obtain the punched aluminum-plastic film; h. Top and side sealing: Place the core into the punched aluminum-plastic film, and perform top sealing, side sealing, corner pre-sealing, and edge trimming in sequence to obtain a semi-finished battery cell.
7. The method for preparing a high-performance polymer composite lithium battery according to claim 5, characterized in that: When the battery capacity of the semi-finished battery cell in step (1) is ≤3000mAh, the second cycle is baked 4 times, the battery capacity is 3000-5000mAh, the second cycle is baked 5 times, the battery capacity is 5000-7000mAh, the second cycle is baked 6 times, the battery capacity is ≥7000mAh, and the second cycle is baked 7 times.
8. The method for preparing a high-performance polymer composite lithium battery according to claim 6, characterized in that: The weight ratio of N-methylpyrrolidone, polyvinylidene fluoride, carbon black and active substance in step a is (30-50): (3-7): (2-10): (33-64).
9. The method for preparing a high-performance polymer composite lithium battery according to claim 6, characterized in that: In step b, the weight ratio of N-methylpyrrolidone, carboxymethyl cellulose, carbon black, graphene, styrene-butadiene rubber and deionized water is (33-55): (2-6): (4-8): (28-42): (1-3): (20-30).
10. The method for preparing a high-performance polymer composite lithium battery according to claim 6, characterized in that: The parameters of the top seal in step h are as follows: upper mold temperature 190-210°C, lower mold temperature 180-200°C, head pressure 0.3-0.6MPa, and packaging time 3-4s; the parameters of the side seal are as follows: upper mold temperature 175-195°C, lower mold temperature 175-195°C, head pressure 0.3-0.6MPa, and packaging time 2.5-4.0s; the parameters of the corner pre-seal are as follows: upper mold temperature 120-140°C, lower mold temperature 120-140°C, head pressure 0.15-0.3MPa, and packaging time 0.3-1.0s.